The J-Curve in HIV: Low and Moderate Alcohol Intake Predicts Mortality but Not the Occurrence of Major Cardiovascular Events. (1st March 2016) - Wandeler, Gilles; Kraus, David; Fehr, Jan; Conen, Anna; Calmy, Alexandra; Orasch, Christina; Battegay, Manuel; Schmid, Patrick; Bernasconi, Enos; Furrer, Hansjakob
Abstract : Objectives: In HIV-negative populations, light-to-moderate alcohol consumption is associated with a lower cardiovascular morbidity and mortality than alcohol abstention. Whether the same holds true for HIV-infected individuals has not been evaluated in detail. Design: Cohort study. Methods: Adults on antiretroviral therapy in the Swiss HIV Cohort Study with follow-up after August 2005 were included. We categorized alcohol consumption into: abstention or very low (<1 g/d), low (1–9 g/d), moderate (10–29 g/d in women and 10–39 g/d in men), and high alcohol intake. Cox proportional hazards models were used to describe the association between alcohol consumption and cardiovascular disease-free survival (combined endpoint), cardiovascular disease events (CADE) and overall survival. Baseline and time-updated risk factors for CADE were included in the models. Results: Among 9741 individuals included, there were 788 events of major CADE or death during 46, 719 patient-years of follow-up, corresponding to an incidence of 1.69 events/100 person-years. Follow-up according to alcohol consumption level was 51% no or very low, 20% low, 23% moderate, and 6% high intake. As compared with no or very low alcohol intake, low (hazard ratio 0.79, 95% confidence interval 0.63 to 0.98) and moderate alcohol intakes (0.78, 0.64 to 0.95) were associated with a lower incidence of the combined endpoint. There was no significant association between alcohol consumption and CADE. Conclusions: Compared with no or very low alcohol consumption, low and moderate intake associated with a better CADE-free survival. However, this result was mainly driven by mortality and the specific impact of drinking patterns and type of alcoholic beverage on this outcome remains to be determined. Abstract : Supplemental Digital Content is Available in the Text.